The method of contextual immersion in a quasi-professional environment as a tool for the formation and monitoring of the professional competence of future engineers-teachers - Bondarenko, T. (Problems of Engineer-Pedagogical Education, 2021)
The article describes the methodology of contextual immersion in a quasi-professional environment for the formation and monitoring of the professional competence of future engineers-teachers. The difference between the proposed immersion method and the existing immersion methods, in particular, the method of immersion in virtual reality, is considered. The article discusses the issue of future engineers-teachers’ immersion into the process of developing electronic educational resources (EER): a distance learning course, a fragment of a video lecture, a mobile computer test control system; lecture presentations. The development of electronic educational resources is carried out in an environment that is as close as possible to the environment of the professional activity of an engineer-teacher. In this environment, future engineers-teachers are involved in educational activities related to immersion. In this case, the practical orientation of engineering and pedagogical education is strengthened, emphasis is placed on the need to gain experience in activities, the ability to put knowledge into practice. At the same time, teaching becomes active in its nature, i.e. the formation and monitoring of a competence is carried out in the course of students’ practical activities: in the process of creating electronic educational resources. To take into account various options for the manifestation of the competence in contextual immersion, a system of private and generalized indicators has been formed and a model for an integral assessment of the competence has been developed on the basis of a multiparametric assessment for each type of task as well as for each type of assessment. The results of experimental verification of the methodology based on the use of quasi-professional tasks, which were designed in such a way as to maximally correspond to real projects for the development of electronic educational resources, are considered. The directions for further improvement of the methodology of contextual immersion in a quasi-professional environment for the formation and monitoring of the professional competence of future engineers-teachers are outlined.